Extramedullary multiple myeloma involving the liver and periportal lymph node, diagnosed by EUS‐FNA in a patient with cirrhosis. Issue 7 (19th March 2020) - Suo, Liye; Liu, Shujuan; Vega, Ivonne; Thrall, Michael
Abstract: Extramedullary multiple myeloma (EMM) involving the liver as a focal space‐occupying lesion is very rare, especially in the patients with cirrhosis. Here, we report a case of EMM in the liver and periportal lymph node, diagnosed by endoscopic ultrasound guided‐fine‐needle aspiration (EUS‐FNA). A 57‐year‐old male patient, with history of cirrhosis, presented with abdominal pain and pancytopenia. The abdominal magnetic resonance imaging (MRI) demonstrated a 6.5 cm left hepatic mass with a 1.1 cm malignant‐appearing periportal lymph node and diffuse osseous lesions. The cytology specimens from the hepatic mass and the periportal lymph node were obtained through EUS‐FNA without rapid on‐site evaluation (ROSE). The thin‐layer preparations (ThinPrep) showed abundant plasmacytoid cells, which were confirmed to be Kappa‐restricted neoplastic plasma cells by the cell block preparations. Later, his serum level of Kappa light chain was found significantly elevated by flow cytometry, which was identified as monoclonal IgA Kappa light chain by serum protein electrophoresis (SPEP) with immunofixation. The patient was diagnosed as IgA multiple myeloma with extramedullary involvement of the liver and periportal lymph node. This is the first case showing the ThinPrep cytomorphologic features of EMM in the liver and periportal lymph node. This case highlights the importance of distinguishing plasma cells from being hepatocytes and lymphocytes on the ThinPrep and also emphasizes the utility of the cell block in the diagnosis of plasma cell neoplasm.